PERGESERAN POLA INTERAKSI GURU DAN PESERTA DIDIK DI ERA SOCIETY 5.0: KAJIAN LITERATUR - Septiani, Dewi Syifa; Irma Ainni, Irma; Hartanto, Rio Tri; Meliana, Lola; Aswad, Libya Hajar; Fricticarani, Ade (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The Society 5.0 era brings significant changes in various aspects of life, including education. The shift in interaction patterns between teachers and students is one of the main impacts of technology integration in the learning process. The purpose of this study is to analyze the Shift in Interaction Patterns of Teachers and Students in the Society 5.0 Era. The research method used in this study is a qualitative descriptive method with a literature review approach (library research). The research design is in the form of a review of journals published in Sinta 6 to Sinta 1 in the period 2020-2025. The results of the study show that there are still challenges in implementing Society 5.0 in the world of education, especially in terms of the use of technology. By continuing to uphold the principles that will understand in upholding human values ​​and dignity in education, schools and teachers must continue to adapt to technological advances. A mature strategy can make Society 5.0 the foundation of a more competitive, flexible, and inclusive education system.